2022
DOI: 10.3390/w14223656
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Characterization and Analysis of River Morphology Using Long-Term Landsat Imagery and Stream Power

Abstract: Meandering rivers are among the most dynamic Earth-surface systems, which generally appear in fertile valleys, the most valuable lands for agriculture and human settlement. Landsat time series and morphological parameters are complementary tools for exploring river dynamics. Karun River is the most effluent and largest meandering river in Iran, which keeps the Karun’s basin economy, agriculture, and industrial sections alive; hence, investigating morphological changes in this river is essential. The morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…These studies have stressed, in particular, the importance of identifying the different alluvial landforms encountered along the river systems, such as point bars, abandoned channel fillings, natural levees and backswamp deposits, as a key first step in order to predict the amount of underseepage and uplift pressure which develops landward of the river embankment. Aerial/satellite imagery [21,22] is often used to detect morphological factors that may reveal the susceptibility to backward erosion piping of the river embankment system. Work by the U.S. Army Corps of Engineers (USACE) along the Mississippi River (e.g., [22,23]) found that point bar deposits-consisting of low ridges of silty sand/sand with intervening arcuate depressions (referred to as swales) filled with fine-grained sediments-and channel fill deposits are the primary geologic environments for sand boil formation.…”
Section: General Mechanics Of Backward Erosion Piping and Predisposin...mentioning
confidence: 99%
“…These studies have stressed, in particular, the importance of identifying the different alluvial landforms encountered along the river systems, such as point bars, abandoned channel fillings, natural levees and backswamp deposits, as a key first step in order to predict the amount of underseepage and uplift pressure which develops landward of the river embankment. Aerial/satellite imagery [21,22] is often used to detect morphological factors that may reveal the susceptibility to backward erosion piping of the river embankment system. Work by the U.S. Army Corps of Engineers (USACE) along the Mississippi River (e.g., [22,23]) found that point bar deposits-consisting of low ridges of silty sand/sand with intervening arcuate depressions (referred to as swales) filled with fine-grained sediments-and channel fill deposits are the primary geologic environments for sand boil formation.…”
Section: General Mechanics Of Backward Erosion Piping and Predisposin...mentioning
confidence: 99%
“…Topographic characterization studies extend beyond the scope of geomorphometry and terrain analysis, frequently establishing significant connections with other subfields of earth science. Examples encompass tectonics, hydrology, ecology, and geology [42,43]. However, acquiring information related to hydrogeology, tectonics, and fault data in the study area poses significant challenges.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Channel geomorphological changes are usually complex in alluvial sandy-bed rivers, driven by the interactions of multiple factors, such as flow conditions, suspended sediment content and bedload composition and characteristics, of which a more comprehensive understanding has been recognized over the past half century [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. However, in arid and semi-arid regions, all kinds of aeolian sand dunes are the most common landforms and landscapes, e.g., [1,[20][21][22][23][24], where many rivers are tightly coupled and intersected with aeolian sand dunes [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%